Analysis of the Modernizations Efforts of Military Instruments in Brazil, China, India and The Brazilian Strategic Projects - Deywisson Ronaldo Oliveira de Souza; Marcos Aurélio Guedes de Oliveira (Meridiano 47, 2017)
This paper analyses the defense strategies of Brazil, China and India and how they have responded to strategic needs that although they are different in the magnitude of their specific contexts, resemble to each other when they impose reforms to meet the regional and systemic character requirements. Deepens in Brazil, evaluating how the new technologies can break down this low strategic profile and initiate a new phase for the Brazilian strategy defense.